All Sports Bobbers : The Case Study - Zaharia, Rebecca; Ondracek, James; Saeed, M (Journal of Commerce and Trade, 2007)
“All Sports Bobbers” is based on the experiences of Paul Zaharia as told to his daughter, Rebecca “Becky” Zaharia. This case is intended for educational purposes only and is not intended to illustrate either effective or ineffective management practices. The case presents an in-depth analysis of the manufacturing and marketing pros and cons of an overseas business firm. It also gives a portrait of bank’s role in establishing the business.